Pratiques et représentations linguistiques des étudiants de la faculté des Langues appliquées de l’Université française d’Égypte et de leur famille - Catherine Julien-Kamal (Recherches en didactique des langues et des cultures)
The representations that speakers, and particularly learners, have of languages are key to understanding bi / plurilingual situations. Analysis of the family background of students enrolled in the Department of Applied Languages in the French University in Egypt has enabled us, on the one hand, to establish which representations influence first the choice of bilingual study and then that of trilingual study at the university level, and, on the other hand, to highlight their attitudes towards international languages, the reasons for these attitudes (belonging to, or the desire to belong to an elite, socioeconomic reasons, etc.) and their impact on language acquisition.